A Disease Progression Model to Quantify the Nonmotor Symptoms of Parkinson's Disease in Participants With Leucine‐Rich Repeat Kinase 2 Mutation. Issue 2 (12th June 2021) - Ahamadi, Malidi; Mehrotra, Nitin; Hanan, Nathan; Lai Yee, Ka; Gheyas, Ferdous; Anton, Judith; Bani, Massimo; Boroojerdi, Babak; Smit, Hans; Weidemann, Jonas; Macha, Sreeraj; Thuillier, Vincent; et al.
Abstract : Leucine‐rich repeat kinase 2 (LRRK2) inhibitors are currently in clinical development as interventions to slow progression of Parkinson's disease (PD). Understanding the rate of progression in PD as measured by both motor and nonmotor features is particularly important in assessing the potential therapeutic effect of LRRK2 inhibitors in clinical development. Using standardized data from the Critical Path for Parkinson's Unified Clinical Database, we quantified the rate of progression of the Movement Disorder Society–sponsored revision of the Unified Parkinson's Disease Rating Scale (MDS‐UPDRS) Part I (nonmotor aspects of experiences of daily living) in 158 participants with PD who were carriers and 598 participants with PD who were noncarriers of at least one of three different LRRK2 gene mutations (G2019S, R1441C/G, or R1628P). Age and disease duration were found to predict baseline disease severity, while presence of at least one of these three LRRK2 mutations was a predictor of the rate of MDS‐UPDRS Part I progression. The estimated progression rate in MDS‐UPDRS Part I was 0.648 (95% confidence interval: 0.544, 0.739) points per year in noncarriers of a LRRK2 mutation and 0.259 (95% confidence interval: 0.217, 0.295) points per year in carriers of a LRRK2 mutation. This analysis demonstrates that the rate of progression based on MDS‐UPDRS Part I is ~ 60% lower in carriers as compared with noncarriers of LRRK2 gene mutations.